Philosophical and Ethical Foundations of Systems Thinking - Debora Hammond (tripleC: Communication, Capitalism & Critique)
Drawing on more than a decade of research on the social implications of systems thinking, as well as practical experience in integrative, community-based approaches to education, this paper is an inquiry into philosophical and ethical considerations growing out of recent developments in systems thinking. In his foundational work on general system theory, Ludwig von Bertalanffy distinguishes between three general developments in the systems field: systems technology, systems science, and systems philosophy. These three dimensions of systems thinking each nurture distinct and often widely divergent theoretical and practical orientations. In his abstract for this session, Gary Metcalf asks whether the systems approach really has anything to offer. Science is a form of social feedback; it has created an enormous body of knowledge about the world and shaped humanity’s understanding of the nature of our collective reality. Knowledge then informs action. Assumptions built into scientific frameworks condition certain kinds of actions, as Bertalanffy has noted. Systems thinking as science nurtures a way of thinking that engenders a different kind of practice; systems as philosophy cultivates an ethic of integration and collaboration that has the potential to transform the nature of social organization. Although humanity still has a lot to learn about living more harmoniously and sustainably, systems thinking has made significant contributions in this direction in many fields, both theoretical and practical. The challenge is to integrate what we have learned, to communicate these insights to a larger audience, and to nurture institutional practices that honor the ethical principles inherent in the systems view.